A wrinkle in time : the effect of Persicaria senegalensis (Meisn.) Soják on the maintenance of the dermal matrisome in photoageing skin - Lall, Namrita (University of Pretoria, 2024)
Thesis (PhD (Medicinal Plant Science))--University of Pretoria, 2024.